Effect of guanethidine, hemicholinium and mebutamate on the hypertensive response to eserine and catechol amines - Varagić, V. (1962)
Guanethidine, hemicholinium and mebutamate were used to study the site and mechanism of the hypertensive response to eserine in the rat. Guanethidine was found to block very effectively the hypertensive effect of eserine and to produce at the same time a very strong potentiation of the response to catechol amines. Hemicholinium, after a certain latent period, also blocked the effect of eserine, at the same time leaving the response to adrenaline and noradrenaline intact. Mebutamate was also found to block the effect of eserine. The results of the present experiments suggest that eserine produces a central adrenergic activation in the rat.